An Analysis of Social Aspects Pale Horse Pale Rider by Anne Porter 1969 - Ali, Muhammad Ilham; Posumah, Jenie; Wardatul Jannah Husain, Sabrina (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This article explains the importance of character awareness as an essential initial formation of human character. Pure character is formed from subjective birth, which is not limited to objective facts. Consciousness is the feeling of "self," the manifestation of "self," and even the equivalent of "self." Conscious activity has two characteristics: liquidity and super temporality. Consciousness is not bound by time, which is constantly flowing and related to the present, past, and future. James also believes that most consciousness is irrational and non-logical. The primary technique used to analyze this research is controlling the flow of consciousness in the novel using the principle of promiscuity. The line that influences the activity of consciousness is promiscuity. Modernism literature focuses on introspection and the most profound activities of the characters, so the author wants to know the characters’ actual thoughts through all levels of the depiction of consciousness, paying attention to the subconscious and subconscious, two of which are primarily abstract and irrational.